CSR commitments, perceptions of hypocrisy, and recovery - Dustin R. Smith; Eric Rhiney (International Journal of Corporate Social Responsibility (JCSR), 2020)
This paper examines perceived hypocrisy when a failure is aligned with prior social performance. It is hypothesized that commitment to a CSR domain creates greater performance expectations thus exacerbating the effects when an aligned failure occurs. Study 1 demonstrates that failure alignment and severity increase perceived hypocrisy which negatively impacts customer evaluations of trust, repurchase intent, and brand attitude. Study 2 evaluates two response strategies of apology and compensation vs. no response. An apology significantly reduced perceptions of hypocrisy only when the failure was unaligned with prior CSR. Compensation significantly reduced hypocrisy in both the unaligned and aligned conditions.
Keywords: 650; Corporate social responsibility; Corporate hypocrisy; Reputation recovery